Tax policy and re-location - Eduardo Haddad; Edson Domingues (European Regional Science Association (ERSA), 2002)
Tax policy proposals in Brazil usually do not take into account effects at sub-national levels. Even when their spatial consequences are taken into account, the available information and analytical tools are not well suited to produce relevant insights to the policymaker. Thus, sound methodological frameworks, built upon consistent regional data, are necessary. This paper deals with important methodological aspects in tax policy/reform studies: tax base endogeneity, changes in relative prices, and sectoral and regional substitution. These aspects can be quantitatively evaluated through inter-regional computable general equilibrium models. Short-run and long-run spatial considerations can be rigorously assessed, producing relevant information to regional planning.
Keywords: 330